Effects of drying surfaces and physical attributes on the development of Aflatoxins (AFs) in red chilies. Issue 2 (2nd January 2022) - Sahar, Najmus; Arif, Saqib; Iqbal, Sajid; Riaz, Sundas; Fatima, Tehseen; Ara, Jahn; Banks, John
Abstract: Evaluation of the suitability of surfaces for sun drying is important to prevent the AFs contamination in any produce. Proper drying can reduce the post‐harvest losses. The study was conducted to determine suitable surfaces for chili drying and the relationship between physical appearance of pods and AFs content to aid management decisions during drying and storage. Chilies dried on ten different surfaces were found to result in varied levels of AFs of between 3.14 and 6.46 ng/g. Chili pods dried on green net (either on or above the ground) for sun drying gave best control of AFs production with lower levels compared to other surfaces. Meanwhile, the AF level in damaged pods (10.11 ± 3.54 ng/g) is three times higher than the AF level, i.e., 3.02 ± 1.17 ng/g in intact pods. The research study concludes that proper drying surface and sorting of pods can minimize the rejections by quality monitoring and trade authorities. Novelty impact statement: The outcome of the present study will help develop better practices and guidelines for the drying of chilies utilizing existing sun drying facilities for the control of aflatoxin contamination. Outcomes of the present study along with similar work on, e.g., Brazil nuts, would serve as a model that could be applied to other crops under risk of aflatoxin contamination such as rice, maize, nuts, and stone fruit. In addition, the results of the project will contribute to the health, wellbeing, and wealth of producers and consumers. The parent xlsx file has also been attached along with this manuscript.